Improved Physiological Gait in Acute and Chronic SCI Patients After Training With Wearable Cyborg Hybrid Assistive Limb - Brinkemper, Alexis; Aach, Mirko; Grasmücke, Dennis; Jettkant, Birger; Rosteius, Thomas; Dudda, Marcel; Yilmaz, Emre; Schildhauer, Thomas Armin (Frontiers in Neurorobotics, 2021)
In recent years robotic devices became part of rehabilitation offers for patients suffering from Spinal Cord Injury (SCI) and other diseases. Most scientific publications about such devices focus on functional outcome. The aim of this study was to verify whether an improvement in physiological gait can be demonstrated in addition to the functional parameters after treatment with neurological controlled HAL® Robot Suit. 15 subjects with acute (<12 months since injury, n=5) or chronic (> 12 months since injury, n=10) incomplete paraplegia (AIS B, n=0 / AIS C, n=2 / AIS D, n=8) or complete paraplegia (AIS A, n=5) with zones of partial preservation participated. Subjects underwent a body weight supported treadmill training for five times a week over 12 weeks using HAL®. At baseline and at the end of the study a gait analysis was performed and additional functional parameters such as 10-Meter-Walk-Test, Timed-Up-and-Go-Test, 6-Minutes-Walk-Test and WISCI II score were collected. Results were evaluated for whole group and individually for acute and chronic subgroups. All functional parameters improved. Differences were also found in physiological parameters such as phases of gait cycle and accompanied by significant improvement in all spatiotemporal and gait phase parameters. The presented study shows signs that an improvement in physiological gait can be achieved in addition to improved functional parameters in patients with SCI after completing twelve-week training with HAL®.